NGENGKLENG DANCE (A SYMBOL OF INNER CRYING RESULTING FROM IGNRED RITUALS): NGENGKLENG DANCE (A SYMBOL OF INNER CRYING RESULTING FROM IGNRED RITUALS) - Indi Khoirun Nisa; Bambang Sugito (Jurnal Pendidikan Sendratasik, 2026)
Abstract: The Ngengkleng dance work is a dramatic dance workinspired by the phenomenon of the postponement of the earth almstradition in Kesiman Village, Pandaan District, Pasuruan Regency. Thepostponement of the ritual gave rise to anxiety and a sense ofcollective guilt in the community which was linked to the Ngengklengphenomenon, a mental disorder experienced by a number of youngwomen. This work depicts the disruption of the balance of humanrelations, nature, and spirituality due to the neglect of ancestraltraditions. The creation of the work uses Jacqueline Smith'sConstruction Method I through the stages of initial stimulation,determining the type of dance, presentation mode, improvisation,evaluation, selection, refinement, and motif development. The form ofthe work is a dramatic dance with a symbolic presentation mode thatcombines elements of dance and theater. The performance structureconsists of an introduction and five scenes that represent theemotional journey of the main character, starting from regret, anger,loss, to the process of recovery through the earth alms ritual. The workwas performed on the proscenium stage of the Cak Durasim Buildingin Surabaya with five female dancers as representatives of theNgengkleng characters. Performance accessories include naturalmakeup, Javanese lurik clothing, miniature tumpeng props, dramaticlighting, and traditional and midi music accompaniment. Throughmovement, expression, and visual elements, this work emphasizes theimportance of tradition as a link between humans and nature,ancestors, and spirituality. Ngengkleng is expected to become amedium for cultural education and social reflection for the community,as well as a creative contribution to the development of dramaticdance in Indonesia.Keywords: Ngengkleng, almsgiving to the earth, dramatic dance.